2020
DOI: 10.1002/jat.4001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral exposure to low‐dose tris(2‐butoxyethyl) phosphate in allergic asthmatic mice

Abstract: Tris(2-butoxyethyl) phosphate (TBEP) is a major organophosphorus flame retardant and has been widely increasing as a substitute for brominated flame retardants. TBEP may have adverse effects on human health; however, its impact on immune and allergic responses remains largely uncharacterized. In this study, the effects of low-dose TBEP comparable with the level of actual human exposure to that of human tolerable daily intake on allergic asthmatic mice were explored. Five-week-old C3H/HeJSlc male mice consumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…To confirm the allergic asthmatic mouse model, we measured the cellular profile of bronchoalveolar (BAL) fluid 48 h after final intratracheal instillation of OVA and serum OVA-specific immunoglobulins (Ig) in the same OVA-immunized mice and described in our previous report [ 11 ]. TBEP treatment increased eosinophils and lymphocytes in BAL fluid of OVA-immunized mice compared to vehicle-treated group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To confirm the allergic asthmatic mouse model, we measured the cellular profile of bronchoalveolar (BAL) fluid 48 h after final intratracheal instillation of OVA and serum OVA-specific immunoglobulins (Ig) in the same OVA-immunized mice and described in our previous report [ 11 ]. TBEP treatment increased eosinophils and lymphocytes in BAL fluid of OVA-immunized mice compared to vehicle-treated group.…”
Section: Resultsmentioning
confidence: 99%
“…TBEP treatment increased eosinophils and lymphocytes in BAL fluid of OVA-immunized mice compared to vehicle-treated group. Moreover, significantly increased OVA-specific IgE and IgG1 were observed in OVA-treated groups compared with the vehicle group [ 11 ]. These results indicate that OVA-treated mice show airway hyperresponsiveness and allergic asthmatic condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While several biological mechanisms may underlie these associations, the exact mechanism has not been clearly elucidated. Laboratory studies report that OPEs are involved in the development and exacerbation of asthma by eliciting increased allergic responses through immunomodulatory effects and oxidative stress, both of which are recognized risk factors in the pathophysiology of asthma. A recent nested case-cohort study among children (ages 9–15 years) also reported significant positive associations between the OPE urinary biomarkers 2-ethylhexyl phenyl phosphate (EHPHP), bis­(2-butoxyethyl) phosphate (BBOEP), and diphenyl phosphate (DPHP) with increased levels of oxidative stress biomarkers (i.e., 8-hydroxy-2′-deoxyguanosine, hexanoyl-lysine, and 4-hydroxynonenal) …”
Section: Introductionmentioning
confidence: 99%